Tropical Red Fruit Blend Foam Mat Drying: Effect of Combination of Additives and Drying Temperatures - Paiva, Yaroslávia Ferreira; Figueirêdo, Rossana Maria Feitosa de; Queiroz, Alexandre José de Melo; Amadeu, Lumara Tatiely Santos; Reis, Carolaine Gomes dos; Santos, Francislaine Suelia dos; Lima, Antônio Gilson Barbosa de; Silva, Wilton Pereira da; Gomes, Josivanda Palmeira; Leite, Daniela Dantas de Farias; Lima, Thalis Leandro Bezerra de (Foods, 2023)
Foam mat drying is a widely used technique for liquid products because it has a number of advantages; however, for an efficient process, the choice of additives and temperatures is extremely important. The objective of this study was to evaluate the effect of additives and drying temperatures on the powders obtained from the blend of tropical red fruits, such as acerola, guava, and pitanga. The foam formulations were prepared by mixing the pulps of the three fruits in equal proportions (1:1:1), all added with 6% albumin and 1% stabilizing agent: E1, gum Arabic; E2, guar gum; E3, gelatin. The combinations were subjected to beating, and subsequently, they were dried in an oven with forced air circulation at four temperatures (50 to 80 °C), with a mat thickness of 0.5 cm. The obtained powders showed low levels of water and water activity and high levels of bioactive compounds, colors with a predominance of yellow, intermediate cohesiveness, poor fluidity, and solubility above 50%. The best temperature for obtaining the powders was 60 °C. The formulation that produced the best results for the production of the tropical red fruit blend powder was the combination of albumin and gelatin.